2019
DOI: 10.1002/pola.29382
|View full text |Cite
|
Sign up to set email alerts
|

Development of a shape‐controlled H2S delivery system using epoxide‐functional nanoparticles

Abstract: Hydrogen sulfide (H2S), an endogenous modulator of signaling processes, has potential as a therapeutic drug or in combination drug therapies. Due to its broad biological impacts and malodorous nature, there is considerable interest in vehicles capable of delivering H2S in a controlled manner. Herein, we report postpolymerization modification of polymers incorporating glycidyl methacrylate (GMA) units to form thiol‐triggered macromolecular H2S donors. By combining this approach with polymerization‐induced self‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Multifunctional anionic and organometallic initiators used in the polymerization of vinyl compounds or dienes can be synthesized by reacting an organolithium with unsaturated aromatic compounds. Many authors [2,[8][9][10] showed, however, that these reactions might lead to the formation of insoluble compounds, when performed in non-polar media, such as cyclohexane, due to association, oligomerization and formation of aggregates. [5] However, certain additives, such as tertiary amines, can prevent the formation of insoluble crosslinked compounds.…”
Section: Effect Of the Polar Modifier At 40 Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Multifunctional anionic and organometallic initiators used in the polymerization of vinyl compounds or dienes can be synthesized by reacting an organolithium with unsaturated aromatic compounds. Many authors [2,[8][9][10] showed, however, that these reactions might lead to the formation of insoluble compounds, when performed in non-polar media, such as cyclohexane, due to association, oligomerization and formation of aggregates. [5] However, certain additives, such as tertiary amines, can prevent the formation of insoluble crosslinked compounds.…”
Section: Effect Of the Polar Modifier At 40 Cmentioning
confidence: 99%
“…[7] The synthesis of bifunctional initiators is often performed by reacting diolefins with n-BuLi in non-polar solvents, such as cyclohexane. However, this technique does not necessarily result in soluble bifunctional initiators with well defined molecular architecture, [8][9][10] also generating initiator fractions that contain more than two active centers and allowing for undesired diolefin oligomerization. [11] Besides, the possible reincorporation of unsaturated chains and chain agglomeration can lead to formation of insoluble fractions that are very poorly reactive.…”
Section: Introductionmentioning
confidence: 99%
“…Though lots of small molecular H 2 S donors have been developed, they usually unable to meet the requirements of in vivo applications, since the stability, water solubility, stimuli-responsive property, and toxicity of donors themselves or their byproducts are difficult to regulate at the small molecule level [ 27 ]. With the purpose to overcome these limits, various biocompatible polymers are utilized to establish H 2 S delivery systems, mainly by physically encapsulating or chemically conjugating H 2 S donors with polymeric carriers such as micelles [ 28 , 29 ], liposomes [ 30 ], nanoparticles [ 31 ], nanofibers [ 32 ], or hydrogels [ 33 ]. The main advantage of these polymeric H 2 S delivery systems is that the H 2 S releasing behaviors including releasing dosage, releasing kinetics, as well as releasing locations are effectively regulated and the biocompatibility is significantly improved without drastically changing the chemical properties of the loaded H 2 S donors.…”
Section: Introductionmentioning
confidence: 99%
“…A novel monomer, 2,2,2‐trifluoroethylamide l ‐arginine methacrylamide, was prepared and copolymerised to yield amphiphilic block copolymers, which can self‐assemble in water to yield micelles. Quinn, Davis, and co‐workers have utilised polymer nanoparticles for the delivery of hydrogen sulphide. The authors report a post‐modification approach utilising glycidyl functionalities as targets to form macromolecular hydrogen sulphide donors.…”
mentioning
confidence: 99%